PENGARUH SUPERVISI AKADEMIK DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU - Nursaodah Aminah; Kartono; Ani Rusilowati (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2022)
This study aims to analyze the effect of academic supervision in improving teachers' pedagogic competence in terms of teacher work discipline. This research method is a meta-analysis that uses secondary data in the form of data from previous research results. Data collection techniques were collected through documentation techniques. The data analysis technique used is descriptive analysis. Based on the results of the analysis of 12 journals, it shows that academic supervision has a significant positive effect on pedagogic competence.